THERE IS NO LEISURE IN TREATING ORTHOGERIATRIC INTERTROCHANTERIC FRACTURE-STABLE FIXATION AND EARLY AMBULATION - A, Mohammed Harris; Kunalan, Shival Sasidaran; Mohamad, Fazir (International Journal of Allied Health Sciences, 2021)
Fracture around hip is one of the most common fractures because of which elderly patients get admitted in an orthopaedics trauma ward. Early surgery became a priority in health systems, but early postoperative physiotherapy also plays a major role in prevention of mortality: independently from surgical timing, patients who did not walk again within 10 days from surgery showed mortality rates higher than those of patients who did. At our centre we aim surgery within 72 hours from time of admission. All patients that were referred to our unit will be operated by trained medical officer, specialist, and consultant. During surgery close manipulative reduction will be attempted, however in difficult cases open reduction and joystick reduction were performed. Aim of reduction is to get near perfect anteromedial cortex continuity. Patients are allowed to fully weight bear immediately after surgery as tolerated with walking frame ambulation. Early mobilization with full weight bearing boosts the confidence of the patients, which has a good overall effect on the well-being, morale and should be recommended following intertrochanteric fracture fixation. In our centre, we started with few cases which were performed by fellow with direct supervision of senior consultant. Now senior medical officer can perform the same with good reduction and are not scared to allow patient to fully weight bear post operatively. In conclusion quality of life will be increased and overall healthcare costs will be decreased in these patients. We would like to share few of the cases with video presentation.